(untitled) (Iranian Journal of Kidney Diseases, 2013)
Intravenous self-infusion of tap water has never been reported in the literature. We present a 24-year-old healthy man who self-administered 2.5 L of tap water over 2 hours and developed acute illness including fever, change of mental status, acute hemolysis, low-grade disseminated intravascular coagulation, and acute kidney injury.